Evaluasi Kebijakan Harga Dasar Gabah: Studi Kasus Panen Raya Tahun 2000 - Afandi, Andik (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2000)
Government gave its support to a price policy with a gabah floor price that was expected to stimulate rice pro-duction. But, during the great harvest 2000, the gabah price fell below the floor price in many paddy production centre. The resultof this research concluded that the gabah floor price is too low. Above all, the goveinment was not pick-aback and implementing the floor price policy seriously. Its prove that cheap food policy, the policy which consumer oriented, is continuing. If this